Control and Operation of the Mmc-Based Drive with Reduced Capacitor Voltage Fluctuations - Diaz-Diaz, M (INST ENGINEERING TECHNOLOGY-IET, 2019)
The modular multilevel converter (MMC) has emerged as a suitable topology for high power drive applications. However, the voltage fluctuations of its floating capacitors increase the control complexity of the converter. In this study, the MMC dc-port voltage is manipulated to regulate the amplitude of these fluctuations to a constant value during the whole frequency range. The proposed approach has several advantages when compared with the conventional ones since it minimises the voltage fluctuation in the capacitor cells. Additionally, it decreases the common-mode voltage at low frequencies and the capacitor rms current, increasing their expected lifespan and reducing the winding insulation damages and the leakage currents in the bearing of the machine. The effectiveness of the proposed control strategy is validated with a laboratory-based prototype composed of 18 power cells, feeding a vector-controlled induction machine.